Procesowe koncepcje negocjacji - Kozina, Andrzej (Process-Oriented Concepts of Negotiations, 2009)
The paper aims at describing business negotiations treated as a process, conducted within or by a company (between its stakeholders, both internal and external ones). Such negotiations processes are of supportive character to the core processes within a company, focused on performing its crucial objectives. Firstly, the general idea of a negotiation process was presented, i.e. treating it as complex venture, comprising many components (subprocesses, phases, steps, and particular activities). Then, three classifications of various approaches of that kind were discussed. Finally, the original author's concept of the description of negotiations as a process was suggested as well as the key issues for subsequent research were pointed out. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 67-72